Code Mixing as a Socio - Psychological Advertising Strategy in the Era of Glocalization - Pareek, Priyanka; Singh, Manju (Indian Journal of Marketing, 2017)
The inventive use of language in different areas by humans makes them creative and innovative. The use of innovative language in advertisements is to hold the attention of consumers and to motivate them to purchase different products. They (advertisers) use different and updated language techniques in advertising; one of them is code mixing (CM), which refers to the mixing of words from different languages in a systematic pattern. This paper intended to provide the role and impact of code - mixing in advertising in India through the interviews conducted from 100 individuals. This will result in understanding the concept of code - mixing from the perspective of ’global advertising strategy’. Additionally, it would help in understanding the cultural identities of other regions and ’social responsibilities’. The results obtained from lexical analysis of code mixed advertisements and readers’ attitudinal surveys showed that the linguistic factors of advertisements are designed keeping multilingual reader’s psychology in mind. Advertisers strategically utilize their linguistic creativity by including different symbolic meanings in their creative linguistic repertoire. It helps in keeping the product memorable. In order to fulfil the purpose of the study, quantitative approach was used to check whether code mixing in advertisements works as a successful language strategy in having imprints on consumers’ minds. The paper provides new explanations using exploratory and descriptive analysis that would be helpful as an evidence to enhance the quality of communication inÂ marketing. It will further provide insights to the advertisers for the development of new marketing policies.